2022
DOI: 10.3390/toxins14050310
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Innervation of the Supraspinatus Muscle Assessed Using Sihler’s Staining: Potential Application in Myofascial Pain Syndrome

Abstract: Despite the positive effects of botulinum neurotoxin (BoNT) injection into the neural arborized area, there is no anatomical evidence in the literature regarding the neural arborization of the supraspinatus muscle. The present study aimed to define the intramuscular neural arborized pattern of the supraspinatus muscle using the modified Sihler’s staining method to facilitate the establishment of safe and effective injection sites in patients with myofascial pain in the supraspinatus muscle. Seventeen supraspin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Spasticity is a major cause of pain, resulting in poor hygiene and difficulties in performing activities of daily living (Lee et al, 2022a(Lee et al, , 2022bYi et al, 2019). The most common spastic pattern in the upper limbs is the elbow flexion with forearm pronation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spasticity is a major cause of pain, resulting in poor hygiene and difficulties in performing activities of daily living (Lee et al, 2022a(Lee et al, , 2022bYi et al, 2019). The most common spastic pattern in the upper limbs is the elbow flexion with forearm pronation.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in the formation of antibodies with lower effectiveness (Hsu et al, 2004;Kinnett, 2004;Lepage et al, 2005). To reduce these negative effects, a lesser amount of BoNT should be injected directly into the neural arborized areas (Lee et al, 2022a(Lee et al, , 2022bRha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we will summarize the Sihler's staining technique and published articles describing the locations of botulinum neurotoxin injections (Lee et al, 2022a; Lee et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Since BoNT inhibits the release of acetylcholine at the neuromuscular junction and myofascial trigger points are associated with motor endplates,7 BoNT should be injected close to the neural arborized area that is adjacent to the motor endplate or nerve ending 8. Many studies have focused on the anatomical location of the neuromuscular junctions of various muscles to establish possible clinical BoNT injection sites,9–11 and results have shown that injections targeting the neural arborized area (endplate-targeted injection), where most neuromuscular junctions are found, are superior to injections targeting the non-neural arborized area 12 13. However, it has been difficult to locate myofascial trigger points and design accurate injections for MPS in the IS, since the actual anatomic location of the neuronal arborization of IS has not been previously elucidated.…”
Section: Introductionmentioning
confidence: 99%